Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Packing Produk Minuman PT. Singa Mas Pandaan - Muhammad Afif (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
AbstractThis study aims to determine the influence of motivation and work environment influence simultaneously and partially and to know which variables that influence dominant between motivation variables and work environment on employee performance of packing beverage products at PT. Lion Mas Pandaan.In this study the primary data obtained through survey results of questionnaires distributed to the study respondents amounted to 32 respondents. In this study used data analysis that is with the test of validity, reliability, multiple linear regression test, simultaneous test and partial test to find out how big influence of each independent variable to the dependent variable.The results of this study proves that based on simultaneous calculation results there is a mutual influence of independent variables that are positive and significant to employee performance variables. While the test results in multiple linear regression and partially showed that each of the independent variables are motivation and work environment have a positive and significant effect on the dependent variable that is the employee's performance at PT. Lion Mas Pandaan. Keywords: Motivation, work environment, employee performance